Alpha-synuclein aggregates trigger cardiolipin externalization and mitophagy - Rebeca Martín-Jiménez; Olivier Lurette; Etienne Hebert-Chatelain (Autophagy Reports, 2024)
Accumulation of Lewy bodies in dopaminergic neurons is associated to Parkinson disease (PD). The main component of Lewy bodies appears to be aggregates of alpha-synuclein (α-syn). Several mutations of the gene encoding this protein promote its aggregation. Thus, clustering of α-syn is considered a central event in the onset of PD. An old theory also postulates that mitochondrial dysfunction represents another cause of PD pathogenesis. However, the impact of α-syn aggregates on mitochondria remains poorly understood considering the technical difficulties to discriminate between the different forms of α-syn. In this punctum, we describe our recent work in which we used a newly developed optogenetic tool to control the aggregation of α-syn and examine the impact on mitochondria. This work revealed that α-syn aggregates dynamically interact with mitochondria, triggering their depolarization and leading to cardiolipin translocation to the surface of mitochondria and mitophagy.Abbreviations: α-syn: alpha-synuclein; BNIP3L: BCL2/adenovirus E1B 19 kDa protein-interacting protein 3-like; FUNDC1: FUN14 domain-containing protein 1; IMM: inner mitochondrial membrane; LIPA: light-induced protein aggregation; OMM: outer mitochondrial membrane; PD: Parkinson disease; SNc: substantia nigra par compacta;